If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(-23x + -44) = 41(-4 + 2x) Reorder the terms: 4(-44 + -23x) = 41(-4 + 2x) (-44 * 4 + -23x * 4) = 41(-4 + 2x) (-176 + -92x) = 41(-4 + 2x) -176 + -92x = (-4 * 41 + 2x * 41) -176 + -92x = (-164 + 82x) Solving -176 + -92x = -164 + 82x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-82x' to each side of the equation. -176 + -92x + -82x = -164 + 82x + -82x Combine like terms: -92x + -82x = -174x -176 + -174x = -164 + 82x + -82x Combine like terms: 82x + -82x = 0 -176 + -174x = -164 + 0 -176 + -174x = -164 Add '176' to each side of the equation. -176 + 176 + -174x = -164 + 176 Combine like terms: -176 + 176 = 0 0 + -174x = -164 + 176 -174x = -164 + 176 Combine like terms: -164 + 176 = 12 -174x = 12 Divide each side by '-174'. x = -0.06896551724 Simplifying x = -0.06896551724
| 3.4t+19.36=-4 | | 3+z/3=21 | | -1/3(x-9)=2/3x+3-1/3x-8 | | -u^2-3u=0 | | 32x^2-9/6x-5 | | 25k+40=-15k-80 | | -9z^2+36x=43 | | 7/8x-10=4 | | 4(3x-1)+13=5x+2 | | 32x2-9/6x-5 | | 4x+1=6x+10 | | 2p-8(8p-3)=-224 | | 2f*6g=0 | | 16-r=21 | | 4/5=10/16x | | 7z+1/4=8z+4/9 | | -77x-96=-27-77x | | 52-(8*2/4)+3^2=0 | | 25+x=14 | | 8.1=(3)(x)(1.5) | | 24z^3-44z^2-28z=0 | | 4=18-3 | | 12.50+.40x=14.75+.25x | | -(x+3)=2x | | p^2=14p-24 | | 11x/9(9-5)=3x+3 | | 5(n-4)=-60 | | r/10+=5 | | 40x+30x+446=14890 | | 3x+7=4(x-5) | | 8w+7=-3w-4 | | 8(9x-10)+5=4x-10 |